Effect Of Infrared Therapy And William Flexion Exercise On Activities Of Daily Living Among Older Adults With Non-Specific Low Back Pain - Eka Putri Hikmawati; Fiqi Widyawati; Young Ari Kusworo; Azizah Rahmawati (Journal Hygeia Public Health, 2026)
Background: Non-specific low back pain (LBP) is a common musculoskeletal disorder among older adults and may reduce their ability to perform activities of daily living (ADL). Various physiotherapy interventions have been applied to manage this condition, including infrared (IR) therapy and William Flexion Exercise (WFE). This study aimed to analyze the effects of IR and WFE on ADL among older adults with non-specific LBP and to compare the effectiveness of both interventions. Methods: This study employed a quantitative experimental design using a two-group pretest–posttest approach. A total of 30 older adults with non-specific LBP who met the inclusion criteria were selected through purposive sampling and assigned to either the IR group (n=15) or the WFE group (n=15). Interventions were administered twice weekly for four weeks. ADL was assessed using the Oswestry Disability Index (ODI). Data were analyzed using the Wilcoxon Signed-Rank Test and Mann–Whitney U Test. Results and Discussion: The results showed that IR significantly improved ADL among older adults with non-specific LBP (p=0.000). Similarly, WFE demonstrated a significant effect on ADL improvement (p=0.000). The Mann–Whitney U Test revealed a significant difference between the two interventions (p=0.000). The WFE group had a higher mean rank (21.43) than the IR group (9.57), indicating that WFE was more effective in improving ADL among older adults with non-specific LBP. Conclusion: Both infrared therapy and William Flexion Exercise significantly improved ADL among older adults with non-specific LBP. However, William Flexion Exercise demonstrated greater effectiveness than infrared therapy in enhancing ADL performance.